NIPT‐based screening for Down syndrome and beyond: what do pregnant women think?. (30th March 2015) - van Schendel, Rachèl V.; Dondorp, Wybo J.; Timmermans, Danielle R. M.; van Hugte, Eline J. H.; de Boer, Anne; Pajkrt, Eva; Lachmeijer, Augusta M. A.; Henneman, Lidewij
Abstract Objective The aim of the study is to study pregnant women's views on noninvasive prenatal testing (NIPT) for Down syndrome and the potential to test for a broader range of conditions. Methods An online questionnaire available on the Dutch pregnancy fair website was completed by 381 pregnant women. Results Of the women, 51% expressed interest in having NIPT, including 33% of women who had declined first‐trimester screening. The majority (73%) thought that the uptake of screening would increase with NIPT. Most women agreed that testing for life‐threatening (89%), severe physical (79%), or severe mental (76%) disorders should be offered. A minority (29%) felt that prenatal screening should also be offered for late‐onset disorders. Most (41%) preferred to have a free choice from a list of disorders, 31% preferred a 'closed offer', and 26% preferred choosing between packages of disorders. Although most women (76%) thought that screening for a broad range of conditions would avoid much suffering, 39% feared that it would confront couples with choices, the implications of which would be difficult to grasp. Conclusion The results suggest that the uptake of screening will increase with NIPT. If NIPT will be offered for a broad range of conditions, it is crucial to find a way that facilitates rather than undermines well‐informed decision‐making. © 2015 John Wiley & Sons, Ltd.